Amine grafted mesoporous silica por CO2 capture - Serrano, Melisa Romina (2020)
Three-aminopropyltriethoxysilane modified MCM-41 mesoporous silicas were synthesized by grafting the organic groups on the support surface, using different molar ratios of SiO2:Aminosilane. The synthesized solids were characterized by N2 adsorption, XRD, FTIR and TG-DTA. MCM-41 has a specific surface area of about 1500 m2/g, while that of the functionalized materials falls around 600 m2/g, showing a tendency to decrease as the content of the functionalizing agent grows. The N2 adsorption isotherms of pure and functionalized materials are characteristic of mesoporous type IV materials. The structural properties were studied by FTIR and XRD. TG-DTA studies allow analyzing the thermal stability of the materials and determining the deposited amine content. The aminosilane modified mesoporous silica materials increase the CO2 adsorption capacity compared to that of the pure MCM-41. The results obtained are well interpreted by Freundlich physicochemical model and the model parameters show a linear correlation with APTES molar content in the samples.